2001
DOI: 10.1176/appi.ajp.158.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Startle Reactions to Acoustic Stimuli in Patients With Obsessive-Compulsive Disorder

Abstract: Patients with OCD were excessively responsive to startle-eliciting stimuli. This effect may be associated with the development or maintenance of OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 9 publications
4
52
0
Order By: Relevance
“…spiders), while in generalized anxiety disorder the absence of a specific feared object is characteristic. Recent experimental evidence from startle studies suggested that in contrast to phobic patients, panic disorder, PTSD, and OCD patients do not show increased sensitivity to specific fear-cues, but rather to the general experimental setting (Morgan et al 1995;Grillon and Ameli 1998;Kumari et al 2001; see also Lang et al 1998, for a similar argument). Since these patients exhibit normal fear-potentiated startle, but increased "baseline" startle, the study of the psychopharmacology of contextual manipulations in addition to cue-specific ones is important (Grillon et al 1999;Ameli et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…spiders), while in generalized anxiety disorder the absence of a specific feared object is characteristic. Recent experimental evidence from startle studies suggested that in contrast to phobic patients, panic disorder, PTSD, and OCD patients do not show increased sensitivity to specific fear-cues, but rather to the general experimental setting (Morgan et al 1995;Grillon and Ameli 1998;Kumari et al 2001; see also Lang et al 1998, for a similar argument). Since these patients exhibit normal fear-potentiated startle, but increased "baseline" startle, the study of the psychopharmacology of contextual manipulations in addition to cue-specific ones is important (Grillon et al 1999;Ameli et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Potentiation of fear-related defense (e.g. startle) behaviours coordinated by the amygdaloid complex and associated structures has also been demonstrated in anxious children (Waters, Lipp and Spence, 2005), children at greater risk of developing anxiety due to parental anxiety (Grillon, Dierker and Merikangas, 1998) and numerous adult populations (PTSD: ; obsessive-compulsive disorder (OCD): Kumari et al, 2001;panic disorder: Grillon et al, 1994;and individuals with subclinical levels of social anxiety: Cornwell et al, 2006;Garner et al, 2008).…”
Section: Concurrent Neuroimaging: Implications For Neuro-cognitive Momentioning
confidence: 99%
“…In fact, the ASR may be increased in subjects suffering from post-traumatic stress disorders (Morgan et al, 1996;Shalev et al, 2000) and during anticipatory anxiety (Grillon et al, 1991) and in several classes of anxiety disorders (Jetty et al, 2001;Kumari et al, 2001). Use of both tests, as in the present study, provides a more complete analysis of the behavioral state to both proximal and distal threats produced by 48-h steroid exposure (Rodgers, 1997).…”
mentioning
confidence: 99%